Uma tese-formação? Mística, fraternuras e utopias da humana docência freireana - Silveira, Melissa Noal da (2021)
This Ph.D. thesis is in the line of Research and Teaching, Knowledge and Development of the Federal University of Santa Maria/RS. By and with this investigation, we aim to understand and resignify with professors of other professors’ and teachers’ co-self(trans)formation, its praxis, and memories, considering mystiques, utopias, and fraternity as possible boosting to the action-reflection-action. Thus, we tension to answer the following research problem: what are the manifestations of co-self(trans)formative professors when they recognize the mystique, the utopias, and the fraternity of the human Freirean teaching with a formation thesis? Methodologically, this study is based on a qualitative approach as a self (trans)formation research in which the coauthors are the subjects in the research, which constitutes a rupture of the dichotomy subject/object. The political methodological approach is inserted in three perspectives, the first is the “non-objectification”, regarding both research and people, the second confers the word as a promoter of possibilities and the third perspective is the hermeneutical interpretation in which the problematizing-dialogue establishes new interpretative constitutions. The construct of the research was created by Investigative Self (trans) Formative Dialogical Circles carried out online. We held eight (8) meetings in which the coauthors, professor Balduíno Antonio Andreola, three (3) of his Ph.D. co-advisees during 2000-2002 at the Federal University of Rio Grande do Sul, the participant-advisor and the researcher-coordinator were the people of and in the research. Nowadays, the coauthors are retired or advise(d) other professors in the post-graduation programs in the institutions they act(ed). The meetings were held to talk about their formation’s paths and the possible influence of the mystique and the utopia in the fraternity of the Freirean human teaching, having their participation in the research and, therefore, in the thesis as formative procedures. The Circles of Culture (FREIRE, 2017) and the Formation-Research (JOSSO 2004, 2010) are the inspiration of the Investigative Self (trans) Formative Dialogical Circles, a propose in which the group Dialogus: education, formation, and humanization with Paulo Freire (UFSM), seeks for a political-methodological reinvention. The epistemology of this research had as central approach the reflections of Paulo Freire in dialogue with other authors to deepen in the education, teaching, praxis, mystique, and fraternity themes. The conceptual rescue was organized by authors whose dialogues were not only possible but also fruitful; Boal (2014), Gadamer (2000, 2015), Josso (2004, 2010, 2016), Henz and Freitas (2015), Santos (2019, 2021), Andreola (2005, 2014, 2019), Boff (1999), Jesus (1992), Silveira (2017) and others. The academic relevance of this research was inserted in the perspective of the dialogue that problematizes the praxis, the memory, and the phenomena that act in teaching formation of co-self(trans)formatives professors and the influences of utopia and mystique in this fraternal construction and full of tenderness. Thus, it was noticed the action-reflection-action in the praxis of and for a possible new education and a possible new world where people recognize and constitute themselves in a permanent process of humanization. The research constructors enabled the comprehension and interpretation of the phenomena in the perspective in which ten dimensions dialogued in the constitution of the thesis-formation: soap bubble, anyalmostwhen, grain of sand and equinox, window, garden, acting friendships, happiness and laugh, meadow, planetary awareness, and lastness. The dialogued Constructuary of this thesis-formation exhibit that Freirean human teaching is performed by people in social-affective-political engagement with fraternity, recognizing themselves in the mystiques of the human congregation and in fights soaked of utopias for a world, for teaching… in where “it is less difficult to love” (FREIRE, 2017).